High levels of antibiotic resistance genes and opportunistic pathogenic bacteria indicators in urban wild bird feces. (November 2020) - Zhao, Huiru; Sun, Ruonan; Yu, Pingfeng; Alvarez, Pedro J.J.
Abstract: This study analyzed fresh feces from three common bird species that live in urban environments and interact with human communities. Antibiotic resistance genes (ARGs) encoding resistance to three major classes of antibiotics (i.e., tetracyclines, β-lactams, and sulfonamides) and the mobile genetic element integrase gene ( intI1 ) were abundant (up to 10 9, 10 8, 10 9, and 10 10 copies/g dry feces for tetW, bla TEM, sul1, and intI1, respectively), with relative concentrations surprisingly comparable to that in poultry and livestock that are occasionally fed antibiotics. Biomarkers for opportunistic pathogens were also abundant (up to 10 7 copies/g dry feces) and the dominant isolates (i.e., Enterococcus spp. and Pseudomonas aeruginosa ) harbored both ARGs and virulence genes. ARGs in bird feces followed first-order attenuation with half-lives ranging from 1.3 to 11.1 days in impacted soil. Although residual antibiotics were detected in the feces, no significant correlation was observed between fecal antibiotic concentrations and ARG relative abundance. Thus, other unaccounted factors likely contributed selective pressure for ARG maintenance. These findings highlight the contribution of wild urban bird feces to the maintenance and dissemination of ARGs, and the associated health risks. Graphical abstract: Image 1 Highlights: Wild urban bird feces contribute to the maintenance and dissemination of ARGs. OPs are abundant in wild bird feces, and some carry both ARGs and virulence genes. Bird fecal ARGs persist moderately and can propagate in impacted soil. Residual antibiotics ingestion by birds may partially contribute to their fecal ARGs. Abstract : Wild urban bird feces contain high levels of antibiotic resistant bacteria and contribute to dissemination of ARGs.